Notaries Responsibilities in Receiving Payment of Tax on Acquisition of Land & Building Rights - Matthew Marcellinno Gunawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Notary is one of the public officials (openbaar ambtenar) who is authorized to make all kinds of agreements in the form of authentic deeds, set the date, keep the deeds and issue grosses, copies and quotations, all of this as long as the act of the deed is not also required to other officials or specifically the obligation. However, it often happens that notaries do things outside their authority, one of which is as the party receiving the deposit of payment of fees for the acquisition of land and building rights. The formulation of this research isknow the responsibilities of the notary in terms of receiving the deposit of payment of taxes on the acquisition of land and building rights, then associated with the appropriate theory in order to draw hypotheses and be supported by research data in the field, as well as civil settlement in the event of a dispute. The method used in this research is the approach method in this writing is normative juridical, the specification of this research is descriptive analytical research. The data source uses secondary data. Data collection techniques using literature study or document study. The data analysis technique used a qualitative descriptive approach. The results of the research on the first and second conclusions. In terms of depositing fees for the acquisition of land and building rights, basically the notary's clients appear to be paying them, but in practice it is often found that notaries are trusted by many appearers/clients to pay the fees for the acquisition of land and building rights from their clients. Related to this, the laws and regulations do not regulate the authority of a Notary as a land deed official to pay land sale and purchase tax from his client or appearer, but if the appearers/clients authorize the notary concerned to represent to pay the land sale and purchase tax in the form of fees for the acquisition of land and building rights to the state treasury, the notary concerned basically does not have the authority to carry out the payment.